Innovations to Sustain Non-Communicable Disease Services in the Context of COVID-19: Report from Pakkred District, Nonthaburi Province, Thailand. Issue 1 (10th June 2021) - Songsermpong, Soraphan; Bunluesin, Sushera; Khomgongsuwan, Panisara; Junthon, Supattra; Cazabon, Danielle; Moran, Andrew E.; Garg, Renu
During the COVI9-19 pandemic, Pakkred hospital in Thailand implemented innovative practices to ensure the continuation of essential medical services for non-communicable disease patients. These practices included decentralized care, telemedicine, home blood pressure monitoring, community delivery of medicines, and facility infrastructure changes. Despite the decrease in hospital visits by hypertension patients during the pandemic, our results suggest that this package of interventions may have contributed to sustained hypertension and diabetes control rates in Pakkred district.